2022
DOI: 10.3389/fpubh.2022.864019
|View full text |Cite
|
Sign up to set email alerts
|

Explore pre-hospital emergency challenges in the face of the COVID-19 pandemic: A quality content analysis in the Iranian context

Abstract: Backgroundpre-hospital emergency is a community-oriented system that responds to the medical needs of the injured or patients with acute and emergency illnesses outside of health care facilities until they are transferred to a medical center. This study aimed to explore pre-hospital emergency challenges in the face of the COVID-19 pandemic.Material and methodsThis study was conducted as a qualitative content analysis in Iran. Using the purposive sampling method, data were collected through in-depth individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…These findings align with a previous studies indicating a surge in demand for ambulance services during the COVID-19 pandemic ( Kinross et al, 2020 ), with increased calls related to COVID-19 cases and a decrease in other emergencies like road accidents ( Lerner et al, 2020 ), which have had a profound impact on their resilience ( Lai et al, 2020 ; Sun et al, 2020 ). The pre-hospital system in Iran has been heavily burdened by the outbreak, with pre-hospital medical staff playing a crucial role in patient management, including screening, primary care, and hospital transfers ( Hadian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings align with a previous studies indicating a surge in demand for ambulance services during the COVID-19 pandemic ( Kinross et al, 2020 ), with increased calls related to COVID-19 cases and a decrease in other emergencies like road accidents ( Lerner et al, 2020 ), which have had a profound impact on their resilience ( Lai et al, 2020 ; Sun et al, 2020 ). The pre-hospital system in Iran has been heavily burdened by the outbreak, with pre-hospital medical staff playing a crucial role in patient management, including screening, primary care, and hospital transfers ( Hadian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the government requested overtime and extended shifts from existing staff to address increased workload. They also recruited recent nursing graduates and medical personnel to fill workforce gaps in pre-hospital emergency care ( Hadian et al, 2022 ). The authors suggest teaching adaptive strategies to enhance the resilience of pre-hospital staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies on the etiologies, risk factors, diagnosis, and management of stroke have been conducted in recent decades, it is still one of the main contributors to the burden of disease worldwide (16). In particularly, China is a country with rapid economic growth in recent years, the lifestyle and living standard of residents have modified.…”
Section: Introductionmentioning
confidence: 99%
“…12 Another study conducted by Hadian et al showed that prehospital emergency medical personnel caring for the COVID-19 patients are suffering from a range of psychiatric problems. 13 Also, a study in Taiwan showed that prehospital personnel who cared for COVID-19 patients had higher burnout scores. 14 Healthcare providers who directly care for COVID-19 patients often see patients' suffering and dying which could lead to their emotional distress and fatigue.…”
Section: Introductionmentioning
confidence: 99%